Provision and Development of Tourism Amenities in the Context of Tourist Comfort and Sustainability in Economic, Socio-Cultural and Environmental Identity of Tourism Villages - HALAWA, Kristiani; LISTYORINI, Haniek (Journal of Tourism Economics and Policy, 2025)
In a destination, in addition to needing tourist attractions, tourists also need amenities for comfort while in a destination. For this reason, destinations need to provide and develop amenities, both tourism facilities and public facilities. In tourism villages, the challenge in providing facilities is a trend for more modern ones so that they are not in line with the values of economic sustainability, socio-cultural and environmental sustainability. This research aims to analyse the provision and development of tourism amenities which aims not only to provide comfort for tourists but also to be able to provide sustainability in the economy, socio-culture and environment. The results of the study show. The research was done with a qualitative method, with in-depth interviews with village governments, pokdarwis managers, culinary actors, tour guides, souvenir and souvenir providers, as well as tourism activity providers, field observations and document studies. The results of the research are 10 tourism facilities provided in the Asinan tourist village that provide comfort and show economic, socio-cultural and environmental sustainability efforts, including special guest receptions, special food and drinks, tour guides, making souvenirs and special souvenirs, rental of typical Rawa activity equipment, homestays, photo spots, activities and art performance facilities. There are a number of obstacles in maintaining sustainability, especially in terms of public awareness of the concept of “SAPTA PESONA” and sustainable tourism. For this reason, the local government and managers strive to increasingly involve the community in the provision of tourism amenities and awareness of sustainable tourism values.